Hydrothermal synthesis of Mo-V mixed oxides possessing several crystalline phases and their performance in the catalytic oxydehydration of glycerol to acrylic acid - Rasteiro, Letícia F. [UNESP]; Vieira, Luiz H. [UNESP]; Possato, Luiz G. [UNESP]; Pulcinelli, Sandra H. [UNESP]; Santilli, Celso V. [UNESP]; Martins, Leandro [UNESP] (Elsevier, 2017)
The one-step oxydehydration of glycerol to acrylic acid over molybdenum and vanadium mixed oxides was investigated. The Mo-V oxide catalysts were prepared by a simple hydrothermal method under different synthesis and calcination atmospheres and were characterized by in situ XRD, TPD-NH3, N2 adsorption/desorption, X-ray absorption near vanadium K-edge spectroscopy and thermogravimetry. The catalytic performance of the samples at different temperatures (290, 320 and 350 °C) and under different gas flow compositions (20% O2 in N2, 100% O2, or 100% N2) revealed that the arrangement of the crystallographic structures of the active phases directly influenced the catalytic performance. It was found that the catalysts heat-treated in oxidizing atmosphere gave superior catalytic results comparing with the catalysts heat-treated in inert atmosphere due to the equilibrium between the crystalline phases MoVO5 and Mo4.65V0.35O14 that contains V+4 and V+5. Catalytic oxydehydration at 320 °C under a flow of 100% O2 gave the best performance, achieving selectivity of 33.5% towards acrylic acid and 100% conversion of glycerol.
Keywords: Acrylic acid; Bifunctional catalysts; Glycerol oxydehydration; Hydrothermal synthesis; Molybdenum-vanadium mixed oxides